Phytoplankton Species Diversity In The Parambikulam-Aliyar Irrigational Canals (Tamilnadu, India) - N. MANICKAM; P. SARAVANA BHAVAN; P. VIJAYAN; G. SUMATHI (International Journal of Pharma and Bio Sciences, 2012)
Phytoplankton biodiversity in the Parambikulam-Aliyar irrigational canals (Latitude 10º15’and 10º30’ N and Longitude 76º50’ and 77º10’ E), Tamilnadu, South India were studied at five stations (S1-S5), Kulanaickenpatti canal (S1), Seelakkampatti canal (S2), Poosaripatti canal (S3), Kongalnagaram canal (S4) and Pethappampatti canal (S5). Totally 22 species of phytoplankton, of which 9 species of Cyanophyceae (blue green algae), 7 species of Chlorophyceae (green algae) and 6 species of Bacillariophyceae (diatoms) were recorded. The total number of species recorded in each station was found to be in the following order, S1 > S2 = S5 > S4 > S3 (20, 15=15, 12 and 8 respectively). Therefore, diversity vise, S1 was superior with more number of species and S3 was inferior with less number of species. As appreciable number of phytoplanktons species were recorded in these irrigational canals, they can be utilized for inland aquaculture purposes if manages properly.